2021
DOI: 10.2478/johh-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

The importance of initial application and reapplication of biochar in the context of soil structure improvement

Abstract: It was shown that the use of biochar provides many benefits to agriculture by improving the whole complex of soil properties, including soil structure. However, the diverse range of biochar effects depends on its physicochemical properties, its application rates, soil initial properties etc. The impacts of biochar, mainly its reapplication to soils and its interaction with nitrogen in relation to water-stable aggregates (WSA) did not receive much attention to date. The aims of the study were: (1) to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
3
16
0
2
Order By: Relevance
“…The economic feasibility of the application of biochar in agriculture depends on two aspects. First, we must demonstrate that biochar, at low and high rates, often contributes to an improvement in many soil quality indicators, an increase in carbon sequestration from the atmosphere, and a decrease in nitrous oxide emission from soils [2,[15][16][17][18][19][20][21][22][23][24][25][26]36,37]. This is an economical benefit of using biochar in the long term.…”
Section: Treatment Sandy Soil Clayey Loam Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic feasibility of the application of biochar in agriculture depends on two aspects. First, we must demonstrate that biochar, at low and high rates, often contributes to an improvement in many soil quality indicators, an increase in carbon sequestration from the atmosphere, and a decrease in nitrous oxide emission from soils [2,[15][16][17][18][19][20][21][22][23][24][25][26]36,37]. This is an economical benefit of using biochar in the long term.…”
Section: Treatment Sandy Soil Clayey Loam Soilmentioning
confidence: 99%
“…Incorporation of biochars into soil can improve soil structure [15], increase organic carbon content [16,17], soil porosity [18,19], saturated hydraulic conductivity [20,21], available water content [22,23], and decrease soil bulk density [24,25]. These favorable biocharinduced changes in the physical properties of soil can increase nitrogen availability [8,26].…”
Section: Introductionmentioning
confidence: 99%
“…Because of high chemical stability, biochar has a great potential to enhance atmospheric carbon sequestration (Laird et al, 2008;Lehmann et al, 2006). Soil amendments such as biochar, composts or their mixtures can decrease soil bulk density (Abd El-Mageed et al, 2021;Hardie et al, 2014), improve soil structure (Ajayi and Horn, 2016;Juriga et al, 2021), increase soil pH (Horák, 2015) cation exchange capacity (Igaz et al, 2018;Jien and Wang, 2013), soil N availability (Haider et al, 2017;Van Zwieten et al, 2010), organic carbon content (Ajayi and Horn, 2016;Šrank and Šimanský, 2020), soil porosity (Blanco-Canqui, 2017;Githinji, 2014), available water content (Głąb et al, 2016;Ibrahim et al, 2013) and saturated hydraulic conductivity (Jien and Wang, 2013;Toková et al, 2020). Syakila and Kroeze (2011) reported that agricultural N2O emission in 2006 reached 23-31% of the global emissions with the main source being nitrogen fertilizer and manure application to soils.…”
Section: Introductionmentioning
confidence: 99%
“…Современные исследования направлены на сопряженную оценку степени взаимосвязей циклов углерода и азота в различных климатических условиях с динамикой температуры, содержания влаги и кислорода, доступных соединений азота и углерода, микробиологической и ферментативной активности, главным образом в самой верхней части генетического профиля почв. Во-первых, инструментальные исследования в целом предусматривают анализ влияния природных и антропогенных воздействий на секвестрацию органического вещества в почвах и их илистых фракциях (52,53). Интенсивность секвестрации и степень закрепления углерода в генетических профилях почв в наибольшей степени обусловлены количеством и минералогическим составом их илистой фракции, содержанием гидроокиси железа при различных окислительно-восстановительных, гидрофизических, теплофизических, биохимических и микробиологических условиях.…”
unclassified
“…Первоначальное, а также повторное применение биоугля приводило к улучшению структуры почвы. Увеличение содержания почвенного органического вещества за счет первоначального и повторного внесения биоугля значительно поддерживало стабильность почвенных агрегатов, в то время как органическое вещество на основе гуминовых веществ не обеспечивало такой стабильности (52,57).…”
unclassified